ETHNOMATHEMATICS IN LOCAL WISDOM: STUDI KASUS PADA KOSTUM BEBEGIG SUKAMANTRI CIAMIS - Repita Wulansari; Adang Effendi; Lala Nailah Zamnah (Interdisciplinary International Journal of Conservation and Culture, 2025)
This research aims to explore the mathematical concepts embedded in the traditional costume of Bebegig Sukamantri, Ciamis. The study is motivated by the importance of connecting mathematics learning with local culture through an ethnomathematics approach. The research employed a qualitative case study design. Data were collected through direct observation, interviews with cultural practitioners, and documentation. The findings reveal that the Bebegig costume incorporates several mathematical concepts, including geometry, transformations (translation and reflection), arithmetic sequences, piecewise functions, and statistics. The study concludes that ethnomathematics can serve as a bridge between culture and mathematics education and has the potential to be applied as a contextual learning medium. The implications of this research highlight the importance of preserving local culture as a source of mathematics learning and the need to integrate ethnomathematics into the educational curriculum.